P77 Is post-TIPSS encephalopathy a bigger burden than anticipated? How can we manage this in practice?. (19th June 2022) - Hicks, Amy; Abouda, George; Corless, Lynsey
Abstract : Introduction: TIPSS (Transjugular Intrahepatic Portosystemic Shunt) procedures are becoming increasingly common, both for management of variceal bleeding and control of refractory ascites. Post-TIPSS encephalopathy is a common complication and the optimal cohort to undergo a successful TIPSS is still being defined. Methods: We audited all TIPSS procedures performed at our centre from 2017 to 2021 to assess outcomes and review local practice. Information on patient demographics, liver disease aetiology and severity, work-up for TIPSS, complications, and outcomes including death and need for liver transplantation were gathered. Results: 38 procedures were undertaken in total. 22 were emergency cases, 12 were pre-emptive procedures for secondary prevention of variceal bleeding, and 4 were performed for refractory ascites. 58% of patients were male, with median age 57 years (range 36 -76 years) and median MELD score 16 (range 7 – 31). Alcohol related liver disease (ArLD) was the commonest aetiology (63% patients). 85% of patients requiring emergency TIPSS had ArLD, and 88% of these were still consuming alcohol. Only a minority received thorough work-up including BNP measurement and documented objective assessment of hepatic encephalopathy (HE). There was a high rate of post-TIPSS HE, affecting 60% of patients surviving to hospital discharge, and 61% of those required re-admission as a result. Longer-term follow-up confirmed that HE resolved in 17% of these patients, the majority (55%) had controlled grade 1-2 HE, and 28% patients continued to have significant symptoms. Smaller stent size (8mm) appeared to be associated with reduced incidence of encephalopathy, although this was not statistically significant (72% 8mm vs. 92% 10mm, p =0.16). Survival was 79% at 30-days (all deaths in emergency TIPSS group), and 61% at 1-year. No deaths were directly attributable to the procedure. Conclusions: This audit provides an insight into practices within a Level 2 Hepatology unit. Whilst TIPSS is a lifesaving procedure for many individuals, the burden of post-TIPSS HE remains high, with this cohort appearing to have a higher incidence than current best estimations in the 2020 BSG TIPSS Guidelines. Appropriate patient selection, work-up and counselling about the expected complications of the procedure are paramount. We are now introducing a patient information leaflet to educate patients about the risks and benefits of the procedure, incorporating a number connection test, and await with interest results of forthcoming national TIPSS studies, which should provide valuable information on true prevalence across the UK.